Meet me under the mistletoe eaudiobook - Bayliss, Jenny (Penguin Audio, 2022)
A city bookshop owner heads to the English countryside for a holiday reunion—only to face her childhood enemy. Elinor Noel—Nory for short—is quite content running her secondhand bookshop in London. Forever torn between her working-class upbringing and her classmates’ extravagant lifestyles at the posh private school she attended on scholarship, Nory has finally figured out how to keep both at equal distance. So when two of her oldest friends invite their whole gang to spend the time leading up to their wedding together at the castle near their old school, Nory must prepare herself for an emotionally complicated few days. The reunion brings back fond memories, but also requires Nory to dodge an ill-advised former fling. When she falls quite literally into the arms of Isaac, the castle’s head gardener, who has nothing but contempt for the "snobby prep school kids," the attraction between them is undeniable. And as Nory spends more time with Isaac during the wedding festivities, she finds herself falling hard for the boy she used to consider an enemy. Nory and Isaac explore their common ground, but pressures mount on all sides, and Nory must decide what kind of life she wants to live and what sort of love is worth the risk . . .